Investigating the Inhibiting Factors in Speaking English Faced by Senior High School Students in Singaraja - Suryani, Ita; Suarnajaya, Wayan; Pratiwi, Astiti (International Journal of Language Education, 2020)
This study had purposes of exploring the factors inhibiting the students in speaking English and knowing teachers perception toward the factors inhibiting the students in speaking English as a foreign language. It was done to overcome students problems in learning the target language ans solve students problems in learning to speak. Descriptive qualitative research was chosen as a research design in conducting this study. It also invloved students and teacher as the subjects of this study. This study proposed twelve factors inhibiting the students in speaking derived from two main factors such as affective and cognitive factor. Shyness, lack of motivation, self-confidence, self-esteem, feeling toward interlocutor, feeling toward topic, and self-concsiousness were the sub-factors under affective factor. Grammar, pronunciation, vocabulary, familiarity of the genre, and knowledge of the topic were considered as cognitive factor. The result of the study showed that the two main factors, affective and cognitive factors, appeared to inhibit the students in learning to speak English as a foreign language. All of the sub-factors categorized as affective factor had revealed to be the factors inhibiting the students in speaking. The result also found that grammar, pronunciation, and knowledge of vocabulary were the factors inhibiting the students in speaking. In addition, the students also got more influence from affective factor as the first main factor inhibiting the students in learning to speak English. The result also showed that the teacher had positively agreed that the inhibiting factors as mentioned earlier also inhibited the students in learning to speak English as a foreign language. In the end, the teacher should also consider the result of the research as the consideration in designing the activity in the process of learning to speak English as a foreign language which would help the students to overcome their speaking problems.